Advances in mass spectrometry (Elsevier Science, 1998)
The CD-ROM contains 300 papers from the oral and poster presentations, a book section comprising the entire contents of the hardbound book version of the conference, an abstract book with an electronic version of the conference abstract book, a video of the closing lecture given by professor R. Graham Cooks and a set of photographs taken during the conference.